EVALUACIÓN PARCIAL DE LA FIDELIDAD EN LA IMPLEMENTACIÓN DEL TRATAMIENTO PREVENTIVO DE TUBERCULOSIS EN PERSONAS QUE VIVEN CON VIH EN PARAGUAY: UN ESTUDIO DE CIENCIA DE IMPLEMENTACIÓN. - Duarte-Zoilan, Derlis; Arbeláez Montoya, María Patricia; Benjumea-Bedoy, Dione (Revista Peruana de Medicina Experimental y Salud Pública, 2026)
Objectives. To evaluate self-reported adherence to the essential components of tuberculosis preventive treatment (TPT), as an estimate of partial implementation fidelity, and to explore the moderating factors influencing its implementation in two referral services in the Central Department, Paraguay. Materials and methods. A descriptive observational mixed-methods study with a convergent parallel design (January–May 2023) was conducted in two referral centers for people living with HIV. Partial implementation fidelity was estimated through self-reported adherence to the content and frequency dimensions of TPT implementation according to the National Tuberculosis Guide. Semi-structured interviews were conducted with key stakeholders to identify barriers and facilitators. Results. 11/13 physicians and 10 key stakeholders participated. Overall TPT fidelity was low (50.0%). Adherence to content was moderate (64.2%), while adherence to frequency was low (31.3%), evidencing a gap between perceived importance and clinical practice. The awareness/education component showed the lowest performance. The main barriers were identified in the internal environment, including organizational fragmentation between TB/HIV programs, limited resources, absence of operational protocols, and communication deficiencies. At the individual level, erroneous beliefs and low self-efficacy were identified. As facilitators, national normative alignment and the willingness of stakeholders to strengthen implementation were observed. Conclusions. Low fidelity reflects mainly organizational and process failures, which highlights the need for facilitation strategies, interprogrammatic articulation, and capacity strengthening to achieve sustained implementation.